Long Term Effect of Low Frequency Tapping Systems Applied to Rubber Tree (Hevea brasiliensis), Clone RRIT 251, on Agronomic Performance in Upper Southern Thailand - Chotiphan, Rawiwan; Musigamart, Natedao; Suwannalert, Soodprasong; Chehsoh, Jirasak; Lerksamran, Tucksin; Lacote, Regis; Sajjaphan, Kannika (Trends in Sciences, 2023)
Clone RRIT 251, a primary clone, was developed by RAOT (Thailand) with promising high yield potential. Low frequencies of tapping (LFT) was tested using 8-year-old trees to characterize the performance of the clone RRIT 251 under such latex harvesting systems. The aim of the study was to assess the response of the yield to LFT related to some biochemical indicators of the latex cells’ metabolism. The experiment was established at the Sithiporn Kridakorn Research Station of Kasetsart University, Prachuap Khirikhan Province, Thailand. The experimental randomized Fisher block design consisted of the 3 treatments. These were abbreviated to T1: S/2 d2 opening BO-1 at 1.5 m, T2: S/2 d3 ET 2.5 % Pa1 (1) 6/y opening BO-1 at 1.3 m and T3: S/2 d4 ET 2.5 % Pa1 (1) 8/y opening BO-1 at 1.2 m. Three replications were conducted with 55 trees per treatment in each experimental plot. Analysis of variance (ANOVA; F test) has been used to compare treatments using Duncan’s multiple range test (DMRT) at a significant level of p < 0.05. Results showed that daily yield greatly increased when using lower tapping frequencies. More than 10 years of tapping, panel management and location of the tapping cut on the panel in downward tapping have significantly impacted yield. Tapping on virgin bark at d3 and d4 frequencies gave higher yield than d2 frequency on renewed bark. Good panel management, combined with tailored stimulation and reduced tapping frequency showed greater efficiency. Results were encouraging. It might be considered that these low tapping frequencies systems can be tested by smallholders and then transferred at the farm gate in Thailand. GRAPHICAL ABSTRACT